Prediction the Level of the Electromagnetic Background Created by Constellations of Satellites Near the Earth’s Surface Using Registration Data - V. I. Mordachev; A. S. Svistunou; D. A. Tsyanenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A technique has been proposed for predicting the average intensity of electromagnetic background created near the Earth’s surface by a constellation of communication satellites, taking into account the number of satellites in the constellation, the satellite total radiated power, parameters of its radiation in the main and side lobes, the orbit altitude and restrictions on the tilt angle of service of ground-based equipment. The results of the analysis of the dependence of the average electromagnetic background levels at the Earth’s surface on the number of satellites in the constellation under various scenarios for the implementation of information services for terrestrial subscriber terminals are presented, conﬁrming the adequacy of the developed approach. It is concluded that the expected levels of electromagnetic background in the microwave range created by megaconstellations of low-orbit communication satellites are many orders of magnitude higher than the levels of electromagnetic background of natural origin, which signiﬁcantly changes the physical characteristics of the habitat.